2019
DOI: 10.1177/1178221819897070
|View full text |Cite
|
Sign up to set email alerts
|

Pain severity and e-cigarette health literacy: the moderating role of sex

Abstract: Although electronic cigarette (e-cigarette) use has increased among adults in the United States, there is still little knowledge of factors that may influence e-cigarette use or beliefs about use. Prior research suggests that health literacy plays an important role in e-cigarette beliefs, including perceived benefits and risks of e-cigarette use, as well as e-cigarette dependence. Yet, limited work has examined risk factors of poor e-cigarette health literacy. From a biopsychological perspective, sex and pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…However, inspection of the form of the interactions indicated that the effect of pain interference on perceived barriers for quitting e-cigarettes, perceived risks of e-cigarettes, and negative expectancies of using e-cigarettes was more pronounced among male e-cigarette users as opposed to female e-cigarette users. Extending prior work on pain severity and e-cigarette use (Smit, Olofsson, et al, 2019; Zvolensky et al, 2019), these data provide preliminary evidence for potentially substantive sex differences in the relation between pain interference and cognitive processes of e-cigarette use and behavior.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, inspection of the form of the interactions indicated that the effect of pain interference on perceived barriers for quitting e-cigarettes, perceived risks of e-cigarettes, and negative expectancies of using e-cigarettes was more pronounced among male e-cigarette users as opposed to female e-cigarette users. Extending prior work on pain severity and e-cigarette use (Smit, Olofsson, et al, 2019; Zvolensky et al, 2019), these data provide preliminary evidence for potentially substantive sex differences in the relation between pain interference and cognitive processes of e-cigarette use and behavior.…”
Section: Discussionsupporting
confidence: 65%
“…Other work has found that the relation between pain severity and e-cigarette outcomes may quantifiably differ as a function of other psychological constructs (such as greater affective vulnerability; Zvolensky et al, 2019) and demographic variables (Smit, Garey, et al, 2019). Indeed, extant research has found that pain severity is related to higher e-cigarette-specific health literacy among female e-cigarette users, but not male e-cigarette users (Smit, Olofsson, et al, 2019), suggesting that pain differentially influences seeking out information about e-cigarettes across men and women.…”
mentioning
confidence: 99%
“…The e-cigarette health literacy reflects the capability to search, understand and utilize relevant information of e-cigarettes to make decisions (Smit et al, 2019). The high-level e-cigarette health literacy of youths and adolescents means that they have a higher risk perception of e-cigarettes and have sufficient knowledge of the relevant health risk of e-cigarettes.…”
Section: The Moderation Role Of E-cigarette Health Literacymentioning
confidence: 99%
“…Pollution is just as unhealthy There are lots of risks in life Everything is unhealthy You have to die of something Everyone acts unhealthy sometimes Not everyone gets sick smoking Know heavy smokers that lived long Medical science will invent something Rather a short/good life than a long/boring life If it were really bad, it would be forbidden I live healthy otherwise Health is not the only thing in life E-cigarette health literacy (Smit et al, 2019) (1 = Probably Not -7 = Probably Yes)…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation